2001
DOI: 10.1080/13642810110066470
|View full text |Cite
|
Sign up to set email alerts
|

Exact solution of the multicomponent Falicov-Kimball model in infinite dimensions

Abstract: The exact solution for the thermodynamic and dynamic properties of the infinite-dimensional multi-component Falicov-Kimball model for arbitrary concentration of d-and f-electrons is presented. The emphasis is on a descriptive derivation of important physical quantities by the equation of motion technique. We provide a thorough discussion of the f-electron Green function and of the susceptibility to spontaneous hybridization. The solutions are used to illustrate different physical systems ranging from the high-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
60
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(63 citation statements)
references
References 20 publications
3
60
0
Order By: Relevance
“…Employing the same numerical technique, Farkasovský investigated the effects of local and non-local 19,20 hybridization on valence transitions. Zlatić et al 21 confirmed that the static excitonic susceptibility diverges at T = 0 in the ordinary FKM (V = 0), from an exact solution of the model in infinite dimension. In dimensions D > 1, a finite f -electron bandwidth breaks the local U (1) symmetry and induce a non-zero polarization even in the absence of d − f hybridization as expected from symmetry grounds.…”
Section: Introductionsupporting
confidence: 48%
“…Employing the same numerical technique, Farkasovský investigated the effects of local and non-local 19,20 hybridization on valence transitions. Zlatić et al 21 confirmed that the static excitonic susceptibility diverges at T = 0 in the ordinary FKM (V = 0), from an exact solution of the model in infinite dimension. In dimensions D > 1, a finite f -electron bandwidth breaks the local U (1) symmetry and induce a non-zero polarization even in the absence of d − f hybridization as expected from symmetry grounds.…”
Section: Introductionsupporting
confidence: 48%
“…5 It has attracted much attention due to the proposal by Portengen et al that the spontaneous excitonic average in the EFKM could be interpreted as evidence of electronic ferroelectricity. 13 Although a variety of more sophisticated treatments 14,15 or more general mean-field theories 16,17 have failed to find the EI phase, the presence of a finite f -electron hopping can stabilize the EI state in the strongcoupling regime. 18,19 Furthermore, it seems likely that in the EFKM with V = 0 the interorbital Coulomb interaction will induce a large "excitonic" renormalization of the bare onsite hybridization potential.…”
Section: Introductionmentioning
confidence: 99%
“…While the static properties of the FKM are well understood at present [5,6] (including the picture of valence transitions), the dynamical properties of the model are still unclear. Even, the spectral properties of the f electrons are not understood satisfactorily nor for V = 0, where only a few exact results are known for the infinite-dimensional systems [7,8]. No exact results are known for nonzero hybridization and T = 0, with the exception of numerical results obtained on very small clusters [9].…”
Section: Introductionmentioning
confidence: 99%